Regional strategy for the implementation in Latin America and the Caribbean of the Madrid International Plan of Action on Ageing (ECLAC SantiagoCL, 2004)
Sets out goals, objectives and recommendations for action in favour of older persons in each of three priority areas adopted in Madrid.
Keywords: AGEING